Mind style and cognitive grammar : language and worldview in speculative fiction - Nuttall, Louise (Advances in stylistics., 2018)
"Mind Style and Cognitive Grammar advances our understanding of mind style: the experience of other minds, or worldviews, through language in literature. This book is the first to set out a detailed, unified framework for the analysis of mind style using the account of language and cognition set out in cognitive grammar. Drawing on insights from cognitive linguistics, Louise Nuttall aims to explain how character and narrator minds are created linguistically, with a focus on the strange minds encountered in the genre of speculative fiction. Previous analyses of mind style are reconsidered using cognitive grammar, alongside original analyses of four novels by Margaret Atwood, Kazuo Ishiguro, Richard Matheson and J.G. Ballard. Responses to the texts in online forums and literary critical studies ground the analyses in the experiences of readers, and support an investigation of this effect as an embodied experience cued by the language of a text. Mind Style and Cognitive Grammar advances both stylistics and cognitive linguistics, whilst offering new insights for research in speculative fiction."--